Mariano BOYANO REVILLA, «Francisco Armanyá. Agustino y obispo ilustrado», Guadarrama, Editorial Agustiniana, 2009, 155 págs. - Díaz Álvarez, Juan (Cuadernos de Estudios del Siglo XVIII, 2009)
SIN RESUMEN